2020
DOI: 10.31229/osf.io/xqy2r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eksistensi Literasi Sebagai Sarana Pelepas Depresi Di Situasi Pandemi

Abstract: Situasi pandemi COVID-19 berlangsung selama kurang lebih sembilan bulan yang tentu saja membuat tak sedikit masyarakat merasa kebosanan dengan rutinitas di rumah saja. Karena situasi ini, interaksi sosial secara langsung mulai berkurang. Berbagai cara dilakukan untuk menghilangkan rasa jenuh dan suntuk seharian, seperti dengan melakukan aktivitas-aktivitas yang dapat memacu hormon endorfin seperti dengan menonton drama ataupun menikmati musik pop Korea, dan ada pula yang menetralkan perasaan suntuknya dengan m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A survey conducted by the Blue Cross Blue Shield Association (BCBSA) in 2017 of 55 million millennials in the US found that depression is the most common health problem experienced by this generation, ranking in the top 10 health problems they are prone to experiencing. Comparative data from various countries also indicates that the millennial generation is the most vulnerable group to experience behavioural disorders (Anggraini, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted by the Blue Cross Blue Shield Association (BCBSA) in 2017 of 55 million millennials in the US found that depression is the most common health problem experienced by this generation, ranking in the top 10 health problems they are prone to experiencing. Comparative data from various countries also indicates that the millennial generation is the most vulnerable group to experience behavioural disorders (Anggraini, 2022).…”
Section: Introductionmentioning
confidence: 99%